Empowering Women Farmers: Case Study on Annu Kanwar’s Amalda Organics - Trilok Kumar Jain (Journal of Advanced Research in Economics and Business Management, 2024)
This case study is based on Ms Annu Kanwar’s initiative to transform women through the transformation of agriculture. Amalda Organics is an initiative to support women. The primary aim of this organisation is women’s empowerment. The overall impact of Amalda Organics on women is analysed in this article. It is an introductory paper and a case study on women’s empowerment.